Comportamento da ferrugem asiática da soja frente a cobertura da superfície foliar e a deposição de fungicida no dossel da planta - Roehrig, Rafael (2017)
The permeation of drops into the canopy of soybean crop is relevant for the chemical control of the diseases, especially the Asian soybean rust that begins its development in the lower part of the plant. Thus, it is crucial to distribute the applied fungicide uniformly throughout the canopy, as well as to promote distribution homogeneity on the leaf, looking for the maximum coverage of the leaf surface, being these factors influenced by the volume of syrup, adjuvants and droplet size. Therefore the application technology can impact on the performance of the agrochemical, especially of fungicides, since those used in the management of the disease, when penetrating,present loco-systemic action, being transported to small distances from the point of deposition. The objective of this study was to determine the impacts caused by fungicide applications with different spectrum of drops, spray volumes and adjuvant combinations, in relation to the productdeposition over the plant, the coverage of leaf surface in different strata of the plant, as well as the behavior of Asian soybean rust epidemic and grain yield. For this purpose, two experiments were carried out, in the first, in a 5x2 factorial scheme, it was evaluated five volumes (40, 70, 100, 130 and 160 L/ha) and the combination of two adjuvants (mineral oil isolated and mineral oil associated with organosiliconated surfactant). In the evaluated portions of the plant, upper, middle and bottom, the number of drops/cm 2 was negatively affected by the reduction in the volume of spray, with larger variations in the lower and middle parts of the plant, impacting on the leaf surface coverage, which did not exceed 13% and 26%, respectively, when used only mineral oil, reaching 17% and 30%, respectively, compared to the combination with the surfactant plus mineral oil, where the improve was responsible for increases of up to 16% in the coverage, which varied by up to 209% in the face of increases in spray volume. The reductions in the volume of the spray reduced the control of Asian rust by up to 2.3 times, when in the absence of the surfactant, and up to 1.7 times when its use, impacting on the leaf area index (LAI), which showed variations on the order of 6.5 times compared to changes in volume and up to 2.8 times when using the surfactant. The grain yield and the mass of one thousand seeds were reduced as the volume of the spray decreased and the reductions were less accentuated when the organosiliconate was used. In the volume of 40 L/ha, were observed differentials in the order of 14% compared to the surfactant, reaching 11 and 9% with the volumes of 70 and 100 L/ha, respectively. The results demonstrate that the leaf surface coverage and the number of drops/cm 2along the plant profile respond to the addition of surfactant and to the increase in the volume of spray, with a direct relationship with the control of Asian soybean rust, impacting on the LAI and in the grain yield. Therefore, there are positive responses in the volume of spray/ha, as well as in the use of the organosiliconated surfactant, which becomes more important the lower volume of spray used. In the second experiment, conducted in 2015/16 harvest, with different cultivars, the objective was to estimate the impacts caused by the change in the droplet spectrum and / or the volume of the spray were estimated in relation to the spray deposits, leaf surface coverage, severity of Asian rust and grain yield. Maintaining the volume of the syrup and changing the spectrum of drops, from fine to medium, similarities were observed regarding spray deposits in the upper, middle and bottom part of the plant, however, there were variations in leaf surface coverage, which was shown to be superior with the use of medium drops, with variations close to 50% in the upper